2016
DOI: 10.7448/ias.19.1.21165
|View full text |Cite|
|
Sign up to set email alerts
|

Primary care clinicians’ experiences prescribing HIV pre‐exposure prophylaxis at a specialized community health centre in Boston: lessons from early adopters

Abstract: IntroductionAn estimated 1.2 million Americans have indications for using antiretroviral pre-exposure prophylaxis (PrEP) to prevent HIV acquisition. For many of these at-risk individuals, the best opportunity to learn about and receive PrEP will be during routine visits to their generalist primary care clinicians. However, few generalist clinicians have prescribed PrEP, primarily because of practical concerns about providing PrEP in primary care settings. The experiences of specialized primary care clinicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…There is on-going discussion about the role of different types of providers in prescribing PrEP, particularly PCPs and infectious disease specialists. [43][44][45][46][47] PCPs are a preferred source of PrEP for many patients, 48,49 and increased trust in a PCP is associated with increased PrEP willingness. 50 This corroborates our finding that many participants felt more comfortable discussing sensitive topics with a provider they already knew and trusted.…”
Section: Discussionmentioning
confidence: 99%
“…There is on-going discussion about the role of different types of providers in prescribing PrEP, particularly PCPs and infectious disease specialists. [43][44][45][46][47] PCPs are a preferred source of PrEP for many patients, 48,49 and increased trust in a PCP is associated with increased PrEP willingness. 50 This corroborates our finding that many participants felt more comfortable discussing sensitive topics with a provider they already knew and trusted.…”
Section: Discussionmentioning
confidence: 99%
“…Another theme we identified in the literature was the belief that being on PrEP would cause individuals to engage in more ''risky'' behavior, such as having sex without a condom or not inquiring about STIs before engaging in sexual activity. 25,[27][28][29]33,34,36,37,39,42,43,45,49,50 Although in most studies worries about risk compensation were minimal, it did emerge as a common theme across the reviewed literature. Specifically, 26% of Washington State providers believed that being on PrEP could increase engagement in risky sexual behavior.…”
Section: Concerns About Behavioral and Health Consequencesmentioning
confidence: 99%
“…49 Moreover, some providers had misgivings about prescribing PrEP, stating that they thought it would lead to an increase in risky behavior and increased HIV transmission, with some providers stating that patients had disclosed increased risky behavior after starting PrEP. 36,37 Some providers even stated that higher-risk individuals would be better off using condoms instead of PrEP. 33 Another study found that fears of risk compensation were more prominent in providers with little PrEP prescribing experience.…”
Section: Concerns About Behavioral and Health Consequencesmentioning
confidence: 99%
“…infectious diseases specialists [91], primary care clinicians [121], and STI clinicians [46]) might encourage a greater number of providers to consider PrEP as part of their clinical purview.…”
Section: Emerging Challengesmentioning
confidence: 99%